PEMBERIAN PAKAN BERBASIS MAGOT DAN LIMBAH SAWI TERHADAP PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Oktamalia, Oktamalia; Hamron, Novita; Sari, Dia Novita; Togatorop, Eny Rolenti (PendIPA Journal of Science Education, 2024)
Fish meal is the main raw material used for feed because it contains high protein. Currently, the fulfillment of fish meal is still supplied from abroad. Indonesia imported 121 thousand tons of fish meal in 2023. This has an impact on the expensive price of feed. In addition, fish meal is produced from fishing in the sea which threatens the sustainability of the fish population. Maggot meal and mustard waste meal as local resources can be a solution in fulfilling alternative protein sources as sustainable fish feed ingredients. The study aimed to evaluate the growth response of tilapia to the effect of adding fish feed ingredients from maggot meal and mustard waste meal. The study used a single factor Completely Randomized Design with four treatments namely, P1: 75% fish meal + 12.5% ​​maggot meal + 12.5% ​​mustard waste meal, P2: 50% fish meal + 25% maggot meal + 25% mustard waste meal, P3: 25% fish meal + 37.5% maggot meal + 37.5% mustard waste meal, P4: 0% fish meal + 50% maggot meal + 50% mustard waste meal. The results showed that the provision of artificial feed based on maggots and mustard waste treatment P4 (0% fish meal + 50% maggot meal + 50% mustard waste meal) provided the best growth performance of tilapia with a daily growth rate of 2.13%, an absolute length of 2.61 cm, an absolute weight of 5.19 g, a percentage increase in length of 32.49% and 100% survival.